On Blowing Trumpets to the Tulips To Prove or Not to Prove the Null Hypothesis - Comment on Bosch, Steinkamp, and Boller (2006). [article]. - Wilson, David B.
The H. Bosch, F. Steinkamp, and E. Boller (2006) meta-analysis reaches mixed and cautious conclusions about the possibility of psychokinesis, The authors argue that, for both methodological and philosophical reasons, it is nearly impossible to draw nay conclusions from this body of research. The authors do not agree that any significant effect at all, no matter how small, is fundamentally important ( Bosch et. al., 2006, p.517), and they suggest that psychokinesis researchers focus either on producing larger effects or on specifying the conditions under which they would be willing to accept the null hypothesis. -- (from the author)